Warehouse sizing algorithm for edification works of construc-tion sector - Andres Mauricio Hualpa Zuñiga; Cesar Amílcar López Bello (Ingeniería, 2015)
This article contains the development of an algorithm applied to the solution of problems of sizing of storage spaces in companies in the construction sector. This problem is justified under the degree of informality that occurs at the time of assigning storage areas, without considering parameters related to stages of construction, the characteristics of the product and the provisions of the work area. In a previous study it is identified that the degree of informality at the moment of assigning storage areas, generates poor rates of capacity utilization and delivery of incomplete orders.